SISTEM REKOMENDASI DRAMA KOREA MENGGUNAKAN METODE USER-BASED COLLABORATIVE FILTERING - William Kristianto; Dyah Erny Herwindiati; Janson Hendryli (Fakultas Teknologi Informasi Universitas Tarumanagara, 2021)
Korean drama is one of the entertainment that is very popular with the public, be it among children, teenager, adults and parents. There is a huge selection of dramas to watch, however, viewers have limited time. Therefore, a recommendation system is used to provide input to viewers in choosing Korean drama series that suits their respective profiles. This recommendation system is made using the User-Based Collaborative Filtering method, where the input of this method is in the form of rating data provided by the user for a list of available Korean dramas. Based on the results of interviews via video calls and questionnaires, this Korean drama application can provide different recommendation results based on user ratings of Korean dramas.